2022
DOI: 10.3389/fped.2022.834039
|View full text |Cite
|
Sign up to set email alerts
|

Eastern India Collaboration on Multisystem Inflammatory Syndrome in Children (EICOMISC): A Multicenter Observational Study of 134 Cases

Abstract: BackgroundFew single center studies from resource-poor settings have reported about the epidemiology, clinical feature and outcome of multisystem inflammatory syndrome in children (MIS-C). However, larger data from multi-center studies on the same is lacking including from Indian setting.MethodsThis retrospective collaborative study constituted of data collected on MIS-C from five tertiary care teaching hospitals from Eastern India. Children ≤ 15 years of age with MIS-C as per the WHO criteria were included. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…In different studies, the median age ranges of MIS-C cases were between the age of 6 and 10 years which is comparable to our study with a median age of 8 years. [14][15][16][22][23][24][25][26] Some studies reported that there is a slight male predominance in MIS-C cases, 14,15,22,26 while others found slightly more female predisposition of MIS-C. 16,24,25 Our study did not find any gender predisposition which was similar to the other studies by Belhadjer et al, 27 Tiwari et al, 28 and Baradaran et al 29 Therefore, considering the data currently available, it cannot be opined that the probability of developing MIS-C is directly related with the sex of the patients. In our study, patients most frequently presented with persistent fever (100%), which is similar to findings in other studies about MIS-C. 15,23,[30][31][32] We observed that all the patients were positive for SARS-CoV-2 antibodies, while in other studies positive serology for was reported in 86 to 100% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In different studies, the median age ranges of MIS-C cases were between the age of 6 and 10 years which is comparable to our study with a median age of 8 years. [14][15][16][22][23][24][25][26] Some studies reported that there is a slight male predominance in MIS-C cases, 14,15,22,26 while others found slightly more female predisposition of MIS-C. 16,24,25 Our study did not find any gender predisposition which was similar to the other studies by Belhadjer et al, 27 Tiwari et al, 28 and Baradaran et al 29 Therefore, considering the data currently available, it cannot be opined that the probability of developing MIS-C is directly related with the sex of the patients. In our study, patients most frequently presented with persistent fever (100%), which is similar to findings in other studies about MIS-C. 15,23,[30][31][32] We observed that all the patients were positive for SARS-CoV-2 antibodies, while in other studies positive serology for was reported in 86 to 100% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, the use of systemic corticosteroids ranged from 65 to 95.65%. [14][15][16][22][23][24][25][26][27][28][29]36 Immunomodulator in the form of IVIG was used in 38.8% (n ¼ 7) of the patients. A systematic review by Ahmed et al 37 showed the use of corticosteroids and IVIG in 52.3 and 76.2% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,[28][29][30] Meanwhile, India, Pakistan and Colombia have reported MIS-C in younger children (median age, 2-7 years). [31][32][33][34] Routine blood testing is initially performed in children with fever. Leukocyte, neutrophil, lymphocyte and PLT counts may easily be obtained using an automatic hematology analyzer.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,28–30 Meanwhile, India, Pakistan and Colombia have reported MIS-C in younger children (median age, 2–7 years). 31–34…”
Section: Discussionmentioning
confidence: 99%